A rose by any other name? Developing a method of collaborative poetics. Issue 4 (1st October 2020) - Johnson, Helen; Macaulay-Rettino, Xander; Banderob, Simon; Lalani, Inara; Carson-Apstein, Emily; Blacher, Ellana
ABSTRACT: This article describes a new method of participatory arts-based research in which poets and social scientists form a collaborative research collective. This collaborative poetics method harnesses participants' skills and knowledge to produce innovative, creative pieces, which can deepen understandings of social scientific issues and communicate this knowledge in engaging, accessible ways. The method was developed in a pilot study in which seven young spoken word poets and one poet/social scientist explored their lived experiences of discrimination. These experiences were elucidated through poetic autoethnographies, which were disseminated in a chapbook and live spoken word performance. Audience feedback indicated that the autoethnographies were powerful and thought provoking. For the co-researchers, the project was a transformative experience, facilitating changes in their focus, exploration, and communication of issues around discrimination and encouraging them to respond differently to instances of discrimination, prejudice, or abuse. The pilot study thus provides strong, preliminary support for the value of the collaborative poetics method.